Role of press in the freedom movement - Bhargava, Moti Lal. (New Delhi : Reliance Pub. House, 1987)
With reference to the Indian press.
Includes indexes.
Bibliography: p. [354]-363.
Keywords: Government and the press -- India; Press -- India -- History; Nationalism -- India -- History; Press and politics -- India -- History; India -- Politics and government -- 1919-1947.